The global economy in turbulent times - Lin, See Yan (John Wiley & Sons Singapore Pte Ltd, 2015)
A leading authority's answer to today's global economic challenges In Global Economy in Turbulent Times, Harvard economist Dr. See-Yan Lin offers his timely and incisive views on today's key economic issues.